A 2D mesoporous photocatalyst constructed by the modification of biochar on BiOCl ultrathin nanosheets for enhancing the TC-HCl degradation activity. (4th December 2019) - Yan, Yan; Tang, Xu; Ma, Changchang; Huang, Hai; Yu, Kesheng; Liu, Yang; Lu, Ziyang; Li, Chunxiang; Zhu, Zhi; Huo, Pengwei
Abstract : The possible separation and transfer of charge carriers in the 15C/BiOCl materials over the TC-HCl degradation process. Abstract : In this paper, a two-dimensional (2D) photocatalyst by the BiOCl ultrathin nanosheet modification of biochar (derived from biomass bamboo leaves) was successfully prepared via a facile one-pot hydrothermal process. The synthesized C/BiOCl photocatalysts showed a satisfactory performance on the degradation of tetracycline hydrochloride (TC-HCl). The enhanced photocatalytic activity originating from the introduction of biochar facilitated the rapid transfer of electrons generated from the defect states of the BiOCl ultrathin nanosheets. Moreover, the more the photo-electrons transferred in biochar, the more the quantities of active ˙O2 − generated during the photocatalytic reaction, which was confirmed from the free radical capture tests. This work can be extended to the modified routes of BiOCl in the further applications of environmental wastewater treatments.